Tackling infrastructural gap in Nigeria: the pension fund option (2018)
The paper reviewed the prospect of using the hugely untapped pension funds to bridge infrastructural financing gap in Nigeria. Infrastructure financing is estimated to cost Nigeria a total investment of USD2.9 trillion over the next 30 years to bring it to the level that can be competitive and self-sustaining. This huge investment outlay is clearly beyond the yearly fiscal operations of government. However, there is a glimmer of hope by way of pension funds, which as at August, 2016, is in excess of N5.9 trillion. This phenomenal growth in pension funds presents a rare opportunity to bridge the nation's current infrastructure gap by leveraging part of the huge pension assets for developmental purposes. The authors argued that there is need to review the regulatory and institutional framework in pension funds administration to make way for a creative use of some of the pension funds to fund infrastructure-creating a veritable profitable investment outlay for the pension funds contributors and at the same time providing the needed funding for critical infrastructure financing in the country.